A greater music - Bae, Su a 1965- (Open Letter, 2016)
"Near the beginning of A Greater Music, the narrator, a young Korean writer, falls into an icy river in the Berlin suburbs, where she's been housesitting for her on-off boyfriend Joachim. This sets into motion a series of memories that move between the hazily defined present and the period three years ago when she first lived in Berlin. Throughout, the narrator's relationship with Joachim, a rough-and-ready metalworker, is contrasted with her friendship with M, an ultra-refined music-loving German teacher, whom, it is suggested, later became her lesbian lover. A novel of memories and wandering, A Greater Music blends riffs on music, language, and literature with a gut-punch of an emotional ending, establishing Bae Suah as one of the most exciting novelists working today."...